Commanding right and forbidding wrong in Islamic thought - Cook, Michael 1940- (Cambridge University Press, 2000)
What kind of duty do we have to try to stop other people doing wrong? The question is intelligible in just about any culture, but few of them seek to answer it in a rigourous fashion. The most striking exception is found in the Islamic tradition, where 'commanding right' and 'forbidding wrong' is a central moral tenet already mentioned in the Koran. As an historian of Islam whose research has ranged widely over space and time, Michael Cook is well placed to interpret this complex subject. His book represents the first sustained attempt to map the history of Islamic reflection on this obligation. It covers the origins of Muslim thinking about 'forbidding wrong', the relevant doctrinal developments over the centuries, and its significance in Sunni and Shi'ite thought today. In this way the book contributes to the understanding of Islamic thought, its relevance to contemporary Islamic politics and ideology, and raises fundamental questions for the comparative study of ethics